Proteomic genotyping of SNP of Complement Factor H (CFH) Y402H and I62V using multiple reaction monitoring (MRM) assays - Kim, Kyoung Lae; Kim, Hyerim; Lee, Youngju; Lee, Cheolju; Joo, Kwangsic; Park, Sang Jun; Park, Kyu Hyung; Park, Seong-Jun; Woo, Se Joon (Nature Publishing Group, 2022)
The single nucleotide polymorphisms (SNPs) of complement factor H (CFH) gene are well-known genetic risk factors for age-related macular degeneration (AMD). To identify whether the measurement of plasma protein concentrations of CFH variants using the multiple reaction monitoring (MRM) assay can determine the genotypes of CFH SNP rs1061170 and rs800292, 120 patients with AMD and 26 controls were included in this study. The number of cases were TT:TC:CC？=？121:24:1 in CFH SNP Y402H and GG:AG:AA？=？72:57:17 in CFH SNP I62V. Plasma concentrations of tryptic peptides were measured using the MRM assay, and tyrosine/histidine (Y/H) and valine/isoleucine (V/I) CFH variant protein ratios were obtained. To discriminate the genotypes by the plasma protein ratios, cut-off values were set for Y/H ratios (TT:？>？4.428; TC: 1.00？4.428; CC:？<？1.00) and V/I ratios (GG:？>？1.09; AG: 0.0089？1.08; AA:？<？0.0089). Correlation analysis revealed that the plasma CFH variant protein ratios and genotypes of CFH were exactly matched (100%) without overlap in the total patients and controls. The measurement of plasma protein CFH variants using the MRM assay can accurately identify the genotypes of CFH SNPs of Y402H and I62V.